2019
DOI: 10.14740/jocmr3702
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Salivary Occult Blood With General and Oral Health Status in Employees of a Japanese Department Store

Abstract: Background The Japanese Ministry of Health started screening for periodontal disease as part of senior health services in 1995. However, only a small number of workplaces conduct regular dental checkups in Japan. Therefore, the prevalence of periodontal disease and other oral health conditions has not been fully determined in workers in Japan. This study aimed to clarify the usefulness of a salivary occult blood test (SOBT) to assess periodontal disease, and to investigate the association of saliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Subjects were asked to refrain from eating and drinking, brushing their teeth, or gargling for 2 hours prior to salivary tests because these factors may cause bleeding and affect the results obtained. [ 5 , 30 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subjects were asked to refrain from eating and drinking, brushing their teeth, or gargling for 2 hours prior to salivary tests because these factors may cause bleeding and affect the results obtained. [ 5 , 30 ]…”
Section: Methodsmentioning
confidence: 99%
“…In Japan, screening for periodontitis has been conducted as part of the health services for individuals aged 40 to 50 years by the Japanese Ministry of Health since 1995, and was extended to those aged 60 to 70 years in 2005. [ 5 ] However, the percentage of individuals undergoing screening is low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saliva tests are easy to conduct and non-invasive, and it has been reported that such tests can produce clinically significant information relating to both systemic and oral disease. [ 15 21 ] Many researchers have reported that saliva-based screening tests are useful for diagnosing periodontitis. [ 15 21 ] As stated above, periodontitis and MetS are closely related and influenced by the same common risk factors [ 22 ] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 21 ] Many researchers have reported that saliva-based screening tests are useful for diagnosing periodontitis. [ 15 21 ] As stated above, periodontitis and MetS are closely related and influenced by the same common risk factors [ 22 ] . Previously, we reported the effectiveness of incorporating dental check-ups into health check-ups and detected a significant association between periodontitis and MetS.…”
Section: Introductionmentioning
confidence: 99%